GEOMETRIC INSPECTION OF PRIMARY AIR FAN ROTOR BLADES USING A LASER SCANNER MEASURING INTRUMENT - Dwinata, Brilliant (TRAKSI, 2024)
New technology related to geometry inspection instruments that have the characteristics of good accuracy, speed, and flexibility are done on Coordinate Measuring Machine. The use of a laser scanner as a measuring instrument has the advantage of the speed of acquisition so that it is suitable for inspecting components that have a complex surface. In this study, the profile measurement method in the Primary Air Fan rotor blade component which was classified as one of the turbo engines was examined. The focus of this research is the description of the tolerance inspection process line profile in general turbo engine blades, specifically the Primary Air Fan blade of the 660 MW Steam Power Plant with refer to the ISO TR 5460 using a 3D laser scanner measuring instrument. ISO TR 5460 is a technical report standard that contains guidelines for verifying geometry tolerance that are described at ISO 1101. The process of inspection of line profile geometry on turbo engine blades with 3D laser scanner measuring instruments generally works by comparing the reference data with measured data. Reference data is a CAD model while measured data is point clouds that have been carried out triangulation / meshing process obtained from the measurement results of measuring objects. The results of the inspection of the line profile tolerance on the Primary Air Fan blade indicate that in each section it was declared not passed the inspection.